Factors Affecting Financial and Non-Financial Performance of MSMEs Through The Use of Social Media - Priliadita Hidayanti; Simanjuntak, Megawati; Hasanah, Nur (School of Business, IPB University (SB-IPB), 2023)
The use of social media for MSMEs is needed so that MSMEs can compete and survive, especially during a pandemic. The purpose of this study was to analyze the influence of trust factors, cost-effectiveness, compatibility, and top management support on the financial and non-financial performance of South Tangerang MSMEs. Data was collected through an online questionnaire using Google Docs. Research variables were measured using a Likert scale. Data processed using descriptive analysis and top two boxes and bottom two boxes. The data that has been processed then analyzed using the Structural Equation Model (SEM). The results of the study found that there were 2 variables that influenced financial and non-financial performance. The compatibility variable has a positive and significant effect on the financial and non-financial performance of MSMEs. Social media can adapt to the needs and business practices of MSMEs which have proven to be a consideration for small business actors in their use. The top management support variable has a positive and significant effect on the non-financial performance of MSMEs. The existence of support from top management for the use of social media in MSMEs affects non-financial performance such as helping relationships with customers and supporting service activities. Based on the test, it found empirical evidence of the effect of compatibility on the financial and non-financial performance of MSMEs and the effect of top management support on the non-financial performance of MSMEs. Keywords: COVID-19, financial performance, MSMEs, non-financial performance, social media